Pelatihan Pembuatan Pupuk Organik Padat dan Cair Berbasis Limbah Lokal di Kelurahan Dana, Kabupaten Muna, Sulawesi Tenggara - La Ode Alwi; Darwis Darwis; Waode Nuraida; Ilian Elvira (Universitas Pahlawan Tuanku Tambusai, 2026)
Farmers’ dependence on inorganic fertilizers in crop cultivation remains high, leading to increased agricultural production costs and a gradual decline in soil quality and fertility over time. Meanwhile, Dana Village, Muna Regency, Southeast Sulawesi, has abundant local waste resources, including crop residues, leaves, livestock manure, and household kitchen waste, which have not been optimally utilized. These materials have the potential to be processed into solid and liquid organic fertilizers that can improve soil fertility and enhance crop productivity. This Community Service Program aimed to improve farmers’ knowledge and skills through training on the production of solid and liquid organic fertilizers based on local waste as an alternative to inorganic fertilizers. The program was implemented through lectures, discussions, and hands-on practice. The results showed increased farmers’ understanding, technical skills, and interest in independently producing and applying organic fertilizers. This activity is expected to be an initial step toward strengthening farmer self-reliance and promoting environmentally friendly agricultural waste management.